2021
DOI: 10.5296/jas.v9i3.18588
|View full text |Cite
|
Sign up to set email alerts
|

Grass and Legume Hays for Sheep: Intake, in vivo Digestibility, and in situ Degradability

Abstract: The objective of this study was to evaluate nutrient intake, in vivo digestibility, and in situ degradability of different cultivars of hay (i.e., [Jiggs] and [Tifton-85] bermuda grass (Cynodon spp.) and [alfalfa] (Medicago sativa) and [stylo] Campo Grande (Stylosanthes sp.)) and nitrogen balance in sheep. We used eight rumen-cannulated F1 Santa Ines × Dorper castrated male sheep with body weights of 35.0 kg in a double 4 × 4 Latin Square experimental design. The intake and total apparent digestibility of nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A mixture of alfalfa hay and concentrate (50:50%) fed to Barki sheep and Balady goats resulted in 58.5 and 53.4% DM digestibility, 58.4 and 53.5% OM digestibility, 68.1 and 62.6% CP digestibility, and 58.4 and 51.1% neutral detergent fiber digestibility in sheep and goats, respectively [ 74 ]. Otoni et al [ 75 ] fed sheep a variety of grass and legume hays and reported in vivo DM digestibility of 47.6, 53.4, 29.3, and 53.2% for Jiggs hay ( Cynodon dactylon ), Tifton-85 ( Cynodon spp. ), stylo ( S. capitata × S. macrocephala ), and alfalfa ( Medicago sativa ) hays, respectively.…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%
“…A mixture of alfalfa hay and concentrate (50:50%) fed to Barki sheep and Balady goats resulted in 58.5 and 53.4% DM digestibility, 58.4 and 53.5% OM digestibility, 68.1 and 62.6% CP digestibility, and 58.4 and 51.1% neutral detergent fiber digestibility in sheep and goats, respectively [ 74 ]. Otoni et al [ 75 ] fed sheep a variety of grass and legume hays and reported in vivo DM digestibility of 47.6, 53.4, 29.3, and 53.2% for Jiggs hay ( Cynodon dactylon ), Tifton-85 ( Cynodon spp. ), stylo ( S. capitata × S. macrocephala ), and alfalfa ( Medicago sativa ) hays, respectively.…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%